2007
DOI: 10.1128/jb.00421-07
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Repetitive Domain of the Magnetospirillum gryphiswaldense MamJ Protein Displays Hypervariability but Is Not Required for Magnetosome Chain Assembly

Abstract: Magnetotactic bacteria navigate along the earth's magnetic field using chains of magnetosomes, which are intracellular organelles comprising membrane-enclosed magnetite crystals. The assembly of highly ordered magnetosome chains is under genetic control and involves several specific proteins. Based on genetic and cryo-electron tomography studies, a model was recently proposed in which the acidic MamJ magnetosome protein attaches magnetosome vesicles to the actin-like cytoskeletal filament formed by MamK, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 40 publications
4
126
0
1
Order By: Relevance
“…MamK protein assembles into actinlike filaments that are involved in the formation of magnetosome chains in Proteobacteria MTB (Komeili et al, 2006;Katzmann et al, 2010;Draper et al, 2011;Ozyamak et al, 2013). An acidic protein, MamJ, interacts with MamK and has important role in chain forming and dynamic turnover of MamK filaments (Scheffel et al, 2006;Scheffel and Schü ler, 2007;Draper et al, 2011). Intriguingly, Mcas has only one copy of mamK and no mamJ despite that the numerous magnetosome chains assembled inside cells (Figure 4).…”
Section: Magnetosome Biomineralizationmentioning
confidence: 99%
“…MamK protein assembles into actinlike filaments that are involved in the formation of magnetosome chains in Proteobacteria MTB (Komeili et al, 2006;Katzmann et al, 2010;Draper et al, 2011;Ozyamak et al, 2013). An acidic protein, MamJ, interacts with MamK and has important role in chain forming and dynamic turnover of MamK filaments (Scheffel et al, 2006;Scheffel and Schü ler, 2007;Draper et al, 2011). Intriguingly, Mcas has only one copy of mamK and no mamJ despite that the numerous magnetosome chains assembled inside cells (Figure 4).…”
Section: Magnetosome Biomineralizationmentioning
confidence: 99%
“…MamJ is an acidic protein associated with the filamentous structure, and it directs the assembly of the BacMP chain (Scheffel et al 2006). Direct interaction between MamJ and MamK has been revealed, and it is proposed that MamJ plays a role in chain assembly and maintenance (Scheffel & Schuler 2007).…”
Section: Protein Analyses Of the Bacmp Membranementioning
confidence: 99%
“…However, MamK is not only a merely rigid backbone, but also has an active function in positioning and concatenating magnetosome chains (Katzmann et al, 2010). MamJ physically interacts with MamK, with two distinct sequence regions involved in binding to MamK, and that direct interaction allow the formation of the magnetosome chain (Scheffel and Schüler, 2007). Interstingly, mamJ and mamK genes are cotranscribed (Scheffel et al, 2006), strengthen the interpretation that both complement each other as two of the main responsible of the arrangement of magnetosomes into chains.…”
mentioning
confidence: 59%
“…MamG, MamF, MamD and MamC are all encoded in the mamGFDC operon. It has been observed that the deletion of the entire mamGFDC operon does not abolish the formation of magnetite crystals, but cells produce crystals that are only 75% of the wild-type size and are less regular than wild-type (Scheffel et al, 2007). These authors also suggested that the MamGFDC proteins have partially redundant functions and control the growth of magnetite crystals in a cumulative manner.…”
Section: Física De La Tierramentioning
confidence: 77%
See 1 more Smart Citation